'They tell us after they've decided things': A cross‐country analysis of unions and digitalisation in retail. Issue 1 (19th December 2022) - Payne, Jonathan; Lloyd, Caroline; Jose, Secki P.
Abstract: The role of trade unions in the social shaping of digital technologies is a vital question for research, public policy and social justice. This article draws on interviews with two unions in the grocery retail sector in the United Kingdom and Norway, and examines their involvement in technology decisions, and whether they can shape better outcomes for workers. By comparing a 'neo‐liberal' economy and a 'Nordic welfare state', the article considers whether stronger institutional power and regulatory supports in Norway provide for greater influence in a sector regarded as challenging for unions. The findings indicate relatively few country differences and help shed light on the factors that enable and constrain unions' role in digitalisation.